Efeito do teor de água na avaliação da compactação do solo causada pelo tráfego agrícola e seu reflexo nos atributos físicos do solo - Fernandes, Barbara Barreto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The changes caused by human activities such as machinery traffic directly affect soil structure, therefore, the importance of assessing soil compaction due to agricultural traffic, as well as the magnitude of the impact of the wheelset on the physical quality of the soil. The study aimed to evaluate the influence of water content in soil penetration resistance evaluation measured by the soil Cone Index (CI), the occurrence and distribution of compression along the soil profile, caused by agricultural traffic, as well as the resulting consequences on soil physical properties. The experiment area was at Lageado Experimental Farm, UNESP/FCA, Botucatu/São Paulo, two different soil type was used, Nitossolo Vermelho distroférrico (NVd) clayey, 50% clay content and Latossolo Vermelho (LV) of medium texture, 25% clay content. Was used an randomized experimental design with the following compaction treatments: T0 = 0; T1 = 1; T2 = 2; T3 = 3; T4= 5 and T5 = 10 consecutive passes of an tractor. An hydraulic-electronic penetrometer was used to measure the soil resistance at 0-0.10; 0.10-0.20; 0.20-0.30 and 0.30-0.40 m in 4 different water content ranging from 17.1 to 24.5% for NVD and 10 to 17.8% for LV. It was also determined the following attributes: soil repression, water infiltration into the soil, bulk density and porosity. The major soil penetration resistance values were detected near the ground shrinkage limit and the treatment with increased intensity agricultural traffic, already in high moisture soil conditions, the soil penetration resistance values were reduced being considered not hindering the growth of roots. The clay soil proved to be the most sensitive to the effect of water content in soil compaction evaluation, the greater variation among samples collected with water content between field capacity (FC) and permanent wilting point (PWP) ...

As modificações causadas por atividades antrópicas como o tráfego de máquinas afetam diretamente a estrutura do solo, por isto, a importância de avaliar a compactação do solo devido ao tráfego agrícola, assim como a magnitude dos impactos do rodado sobre a qualidade física dos solos. O trabalho teve por objetivo avaliar a influência do teor de agua na avaliação de resistência mecânica a penetração do solo medida através do índice de cone (IC), a ocorrência e distribuição da compactação ao longo do perfil do solo causada pelo trafego agrícola, assim como os consequentes reflexos nos atributos físicos do solo. O experimento foi realizado na Fazenda Lageado da UNESP/FCA, Botucatu/SP, sendo selecionadas duas classes de solo, o Nitossolo Vermelho distroférrico (NVd) de textura argilosa, com 50 % de teor de argila e o Latossolo Vermelho (LV) de textura média, com 25 % de teor de argila. O delineamento experimental foi casualizado, com os seguintes tratamentos de compactação: T0 = 0; T1 = 1; T2 = 2; T3 = 3; T4=5 e T5 = 10 passadas consecutivas de um trator agrícola. Utilizou-se um penetrômetro hidráulicoeletrônico para a amostragem da resistência mecânica do solo a penetração nas camadas de 0 a 0,10; 0,10 a 0,20; 0,20 a 0,30; 0,30 a 0,40m em 4 condições de teor de água, que variou de 17,1 a 24,5% para o NVd e de 10,0 a 17,8% para o LV. Também foram determinados os seguintes atributos: recalque do solo, infiltração de água no solo...
Effect of water content in soil compaction assessment caused by traffic agricultural and his reflection in physical attributes of the soil
Keywords: Solos - Compactação; Máquinas agrícolas; Fisica do solo; Soil physics